2012
DOI: 10.1007/s10237-012-0402-y
|View full text |Cite
|
Sign up to set email alerts
|

Vortical flow in the utricle and the ampulla: a computational study on the fluid dynamics of the vestibular system

Abstract: We present a computational study of the fluid dynamics in healthy semicircular canals (SCCs) and the utricle. The SCCs are the primary sensors for angular velocity and are located in the vestibular part of the inner ear. The SCCs are connected to the utricle that hosts the utricular macula, a sensor for linear acceleration. The transduction of angular motion is triggered by the motion of a fluid called endolymph and by the interaction of this fluid with the sensory structures of the SCC. In our computations, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
2
25
0
1
Order By: Relevance
“…All vortices are in the opposite direction to head angular acceleration due to the inertia. The endolymphatic flow regime is consistent with the prediction by Boselli et al (2012). In addition, the velocity profiles can be proved to be a parabolic shape (Fig.…”
Section: Dynamic Responses In Ps and Model Validationsupporting
confidence: 82%
See 1 more Smart Citation
“…All vortices are in the opposite direction to head angular acceleration due to the inertia. The endolymphatic flow regime is consistent with the prediction by Boselli et al (2012). In addition, the velocity profiles can be proved to be a parabolic shape (Fig.…”
Section: Dynamic Responses In Ps and Model Validationsupporting
confidence: 82%
“…All of them found that the responses are positively correlated to stimulation. Simultaneously, mathematical models were introduced, and endolymph and cupular responses to head rotation were explored (Boselli et al, 2012;Damiano and Rabbitt, 1996;Lasker et al, 2008;Oman et al, 1987;Rabbitt et al, 2009;Van Buskirk et al, 1976;Van Egmond et al, 1949). However, the SCCs were usually represented as the torsion pendulum in above mathematical models.…”
Section: Introductionmentioning
confidence: 99%
“…Changing the center of rotation changes the linear acceleration of the system. Linear acceleration, however, does not lead to any flow in the canal [47], such that the total flow u þ u p is independent from the center of rotation. Later, we will exploit this property to validate our computation.…”
Section: Discussion Of the Bgqramentioning
confidence: 97%
“…The total flow which is obtained by adding the particular solution u p ¼ Cr 3 e h to u models the Stokes flow in a semicircular canal of the inner ear induced by an angular acceleration of 120 =s 2 where the center of rotation is at the origin [47,22]. Changing the center of rotation changes the linear acceleration of the system.…”
Section: Discussion Of the Bgqramentioning
confidence: 99%
See 1 more Smart Citation